Penyuluhan Dampak dan Konsekuensi Hukum Judi Online dalam Kalangan Remaja di SMK Taruna Bhakti Depok - Putri, Adinda Alvita; Ariono, Sujud; Hia, Baliterofi; eKO, Dedin Rohmat; Santoso, Santoso; Sutrisno, Andri (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2024)
Real Work Lectures (KKN) are an integral program in higher education to apply knowledge to society. IBLAM students, supported by Garuda Food and expert sources, held a legal outreach activity with the theme "The Impact and Legal Consequences of Online or Slot Gambling among Teenagers" at Taruna Bhakti Vocational School, Depok on June 22 2024. This outreach aims to increase awareness of the risks of online gambling, especially in teenagers. With theoretical presentations, case studies and question and answer sessions, this activity successfully broadens students' understanding of the social, psychological and legal impacts of online gambling. The results show increased awareness and commitment of students to avoid these harmful activities, as well as share information with their peers. This activity emphasizes the importance of education and the role of parents and educational institutions in preventing the spread of online gambling among teenagers.